1975
DOI: 10.1103/physrevlett.35.770
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Difference between Polarization and Analyzing Power inΛ0Production with 6-GeV/cPolarized Protons

Abstract: PHYSICAL REVIEW LETTERS 22 SEPTEMBER 1975 X Y 0 Akimov et al., "Proton-Deuteron Elastic Scattering at Small Momentum Transfer from 50 to 400 GeV/c" (to be published). 2 Y. Akimov et al 0i preceding Letter [Phys. Rev. Lett. 3J5, 763 (1975)]. 3 This is justified by the near factorization of the form factor in elastic scattering (Ref. 1) and by the factorization of the diffractive vertex in the low-mass region (Ref. 2). In a fit of our inelastic data where c was treated as a free parameter, we obtained c = 64 0 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 7 publications
4
50
0
Order By: Relevance
“…The result of opposite directed global polarization at different centralities would be weird, if we assume that polarization comes from the angular momentum. Besides, no experimental polarization measurements before the present ones had observed the opposite-pointing direction of global polarization [1][2][3][4][5][6]. This might be because of the inappropriate choice of momentum space.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The result of opposite directed global polarization at different centralities would be weird, if we assume that polarization comes from the angular momentum. Besides, no experimental polarization measurements before the present ones had observed the opposite-pointing direction of global polarization [1][2][3][4][5][6]. This might be because of the inappropriate choice of momentum space.…”
mentioning
confidence: 73%
“…The nontrivial polarization effect in high energy collisions, since it was first observed in Fermilab with both polarized and unpolarized incident beams [1,2], has been raising people's interest. The hyperon is well suited to measure the polarization because through the decay 0 → p + π − with proton carrying the spin information, the becomes its own spin analyzer.…”
mentioning
confidence: 99%
“…The polarizations have been used widely in studying various aspects of spin physics in high energy reactions [2,3,4,5,6,7]. The discovery of transverse hyperon polarization in unpolarized hadron-hadron and hadron-nucleus collisions in the 1970s led to many subsequent studies, both experimentally and theoretically [8,9]. Phenomenological studies of longitudinal hyperon polarization may be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery [1,2] in 1970s, the surprisingly large transverse polarization of hyperons in unpolarized high energy hadron-hadron and hadron-nucleus collisions has been a standing hot topic in High Energy Spin Physics (see e.g, [1,2,3,4,5,6,7,8,9,10,11,12,13], and the references cited therein.). Experimentally, there are a large number of similar experiments that have been performed at different energies and/or using different projectiles and/or targets and for the production of different hyperons [3].…”
Section: Introductionmentioning
confidence: 99%